Thomas Aquinas Holds Fast: Objections to Aquinas within Today's Debate on Divine Action. (1st September 2011) - Silva, Ignacio
<x xml:space="preserve">Abstract</x> Various authors within the contemporary debate on divine action in nature and contemporary science argue both for and against a Thomistic account of divine action through the notions of primary and secondary causes. In this paper I argue that those who support a Thomistic account of divine action often fail to explain Aquinas' doctrine in full, while those who argue against it base their objections on an incomplete knowledge of this doctrine, or identify it with Austin Farrer's doctrine of double agency – again failing to do Aquinas justice. I analyse these objections, indicating how they do not address Aquinas' doctrine by offering a brief but full account of the latter.